2024
DOI: 10.1099/mgen.0.001224
|View full text |Cite
|
Sign up to set email alerts
|

Virulence genes, resistome and mobilome of Streptococcus suis strains isolated in France

Manon Dechêne-Tempier,
Claire de Boisséson,
Pierrick Lucas
et al.

Abstract: Streptococcus suis is a leading cause of infection in pigs, causing extensive economic losses. In addition, it can also infect wild fauna, and can be responsible for severe infections in humans. Increasing antimicrobial resistance (AMR) has been described in S. suis worldwide and most of the AMR genes are carried by mobile genetic elements (MGEs). This contributes to their dissemination by horizontal gene transfer. A collection of 102 strains isolated from humans, pigs and wild boars in France was subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…Often misclassified in the literature as transposons or plasmids (40), ICEs are also capable of HGT. Studies on enterococci and streptococci showed that these MGEs play a crucial role in the dissemination of ARGs (41). The well-known Tn 916 family was found in many Firmicutes, always carrying the tet(M) gene (4244).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often misclassified in the literature as transposons or plasmids (40), ICEs are also capable of HGT. Studies on enterococci and streptococci showed that these MGEs play a crucial role in the dissemination of ARGs (41). The well-known Tn 916 family was found in many Firmicutes, always carrying the tet(M) gene (4244).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on enterococci and streptococci showed that these MGEs play a crucial role in the dissemination of ARGs (41). The well-known Tn916 family was found in many Firmicutes, always carrying the tet(M) gene (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%